PERAN WANITA KARIER DALAM PEMBANGUNAN KELUARGA SAKINAH PERSPEKTIF MAQASHID SYARIAH - Hikmatullah Hikmatullah; Ruf'ah Abdullah; Fedrik Wardiansyah (Islamic Civil Law Departement of Shari'a Faculty at Islamic State University of Sultan Maulana Hasanuddin Banten, 2023)
Along with the development of changes in the mindset of women who participate actively and participatively in women's careers, it has a positive and negative impact, which results in reduced attention and obligations of women in their households. But keep in mind, that the role of women can also contribute greatly to the welfare and harmony in the family. What are the positive and negative impacts of women who participate actively and participatively in the career world? What is the maqashid shari'ah perspective on the role and contribution of women in the development of the sakinah family? This study uses a descriptive analysis method, namely to analyze and describe the role of women in family development from a maqashid shari'ah perspective. Based on the results of the description in this study, several positive and negative impacts of women who participate actively and participatively in the career world and the implications that the role and contribution of women are very positive in the development of the sakinah family and in accordance with the purpose of marriage, namely those contained in QS. al-Ruum (30) paragraph 21 and Marriage Law No. 1 of 1974 Chapter I Article 1 (forming a happy and eternal family based on the One and Only God), and in accordance with maqashid shari'ah (the purpose of shari'ah), namely hifz ad-din which is to maintain religion in several forms of activities, which include carrying out mahdhah and ghair mahdhah worship, Hifz Al-Nafs is to maintain the soul and body of the family harmoniously and humanely while still paying attention to the needs of a decent life and staying away from unhealthy life habits., Hifz Al-Aql is able to maintain family sense while still paying attention to education both religious education and general education such as implementing government recommendations that send children to school as high as compulsory education for at least 12 years, Hifz an-nasl is to maintain offspring by making family planning programs only used to manage the distance between one child and another, and not only have two children for financial reasons because the sustenance of every child born is guaranteed, and the last hifz al-mal is to maintain property, both her husband's property and hers, because her role and contribution as a career woman can only help the husband to meet or meet the needs family, if not sufficient needs in daily life.